2012
DOI: 10.4161/cbt.13.2.18455
|View full text |Cite
|
Sign up to set email alerts
|

EMMPRIN silencing inhibits proliferation and perineural invasion of human salivary adenoid cystic carcinoma cells in vitro and in vivo

Abstract: Salivary adenoid cystic carcinoma (SACC) is a frequent subtype of salivary gland malignancy, and it has an important biological behavior for perineural invasion (PNI). Extracellular matrix metalloproteinase inducer (EMMPRIN) is a transmembrane glycoprotein that is involved in the invasive property of many malignancies by stimulating matrix metalloproteinase (MMP) expression. The present study was designed to investigate the role and possible mechanism of EMMPRIN in the PNI of SACC using RNA interference (RNAi)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 33 publications
1
17
0
Order By: Relevance
“…Proteins involved in cell-cell adhesion (hemidesmosome proteins B180 and B230, E-and N-cadherin, CDH12, acatenin, mammalian ENA, CD44 and CD24) [93][94][95][96][97][98], migration (matrix metalloproteinase, heparanase, CD147 or extracellular matrix metalloproteinase inducer or Emmprin) [11,[99][100][101][102] and epithelial-mesenchymal transition (NBS-1 and snail)…”
Section: Proteins Involved In Apoptosismentioning
confidence: 99%
“…Proteins involved in cell-cell adhesion (hemidesmosome proteins B180 and B230, E-and N-cadherin, CDH12, acatenin, mammalian ENA, CD44 and CD24) [93][94][95][96][97][98], migration (matrix metalloproteinase, heparanase, CD147 or extracellular matrix metalloproteinase inducer or Emmprin) [11,[99][100][101][102] and epithelial-mesenchymal transition (NBS-1 and snail)…”
Section: Proteins Involved In Apoptosismentioning
confidence: 99%
“…A modified protocol of Transwell cultures was used, based on previous studies (15,16). A Transwell Âź (24 mm) with a 0.4-”m pore polyester membrane insert (Corning, Inc., Corning, NY, uSA) was used to establish the co-culture system.…”
Section: Establishment Of a Co-culture System Between Tumor Cells Andmentioning
confidence: 99%
“…On the other hand, it was demonstrated that silencing of gal-3 in gastric cancer cells downregulated the expression level of MMP-1 and 9 [Kim et al, 2011]. It was shown that silencing of EMMPRIN expression in the human SACC cell line (Salivary adenoid cystic carcinoma) suppressed MMP-2 and MMP-9 secretion [Yang et al, 2012]. Silencing gal-3 in pancreatic cancer cells reduced MMP-2 expression via the Wnt signaling pathway [Kobayashi et al, 2011].…”
Section: Discussionmentioning
confidence: 99%